Together We Build Human Capital - Mishra, A. K. (Apex Journal of Business and Management, 2023)
This editorial highlights the need for adopting a unique practice of publication for building human capital under changing social conditions. The perspective is from the desk of the editor based on experiences, observations, and reviews of published and unpublished literature. By investing in education, skills development, collaboration, and well-being, Society 5.0 can create a human-centered environment that harnesses the potential of individuals to drive innovation, economic growth, and social progress. Embracing these strategies will lead to a more inclusive, sustainable, and prosperous future for all members of society.Apex College is dedicated to building human capital, which is essential for success in Society 5.0, and encourages us to start a unique approach of publication as the Apex Journal of Business and Management. This is the inaugural issue of the Apex Journal of Business and Management consisting of 10 articles and this editorial perspective. It is Apex new initiative for building human capital through extensive research and publication. The editorial provides in brief changes in social conditions and strategies that need to be adopted for building human capital along with highlights on the needs of the journal with unique features in the domain of business, management and social sciences including technology. We request your feedback and end with a wish for happy and prosperous Dashain, Tihar, and Chhath, with a hope to overcome the issue of starvation and obesity from the globe.